2020
DOI: 10.1177/0269215520916851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kinesio Taping and compression stockings on pain, edema, functional capacity and quality of life in patients with chronic venous disease: a randomized controlled trial

Abstract: Objective: The aim of this study was to compare the effects of Kinesio Taping and compression stockings on pain, edema, functional capacity and quality of life in patients with chronic venous disease (CVD). Design: This is a prospective, randomized, controlled, single-blind clinical trial. Setting: The study was conducted in a physiotherapy and rehabilitation unit of a university hospital. Subjects: A total of 62 patients with early-stage CVD were allocated to either an experimental group or a control group. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
0
13
0
5
Order By: Relevance
“…Within 4 weeks, the compression stockings decreased pain and edema more effectively than the Kinesio taping intervention in patients with CVD. 38 In 2018, Klonizakis and colleagues 39 assessed the feasibility of a 12-week supervised exercise program as adjunctive therapy to compression in 39 patients with VLUs. This was a 2-center, 2-arm, parallel-group, randomized feasibility trial.…”
Section: Results Of Scoping Review Of Clevdalmentioning
confidence: 99%
See 1 more Smart Citation
“…Within 4 weeks, the compression stockings decreased pain and edema more effectively than the Kinesio taping intervention in patients with CVD. 38 In 2018, Klonizakis and colleagues 39 assessed the feasibility of a 12-week supervised exercise program as adjunctive therapy to compression in 39 patients with VLUs. This was a 2-center, 2-arm, parallel-group, randomized feasibility trial.…”
Section: Results Of Scoping Review Of Clevdalmentioning
confidence: 99%
“…This study demonstrated that Kinesio taping and compression stockings generated similar improvements in functional capacity and QOL with CVD patients. Within 4 weeks, the compression stockings decreased pain and edema more effectively than the Kinesio taping intervention in patients with CVD 38…”
Section: Results Of Scoping Review Of Clevdalmentioning
confidence: 99%
“…Evaluating the functional capacity that affects the QoL of patients is important. Naci et al 34 reported walking distance of patients with CVI as 438.294 ± 106.32 m in 6-MWT and demonstrated a significant increase in walking distance after calf muscle pumping and diaphragmatic breathing exercises. Moreover, Gürdal Karakelle et al 29 found walking distance of patients with CVI as 470.58 ± 71.52 m. Erdal et al 35 recorded a 386.78 ± 12.34 m walking distance for CVI patients, with an expected percentage of the 6-MWT of 57.66% ± 1.97%.…”
Section: Discussionmentioning
confidence: 99%
“…The self-designed ankle pump movement cognition and compliance status survey questionnaire is used for investigation. The first draft is formulated by the literature review method [10][11][12] and discussed with 5 clinical thrombosis prevention experts.…”
Section: Investigation Methodsmentioning
confidence: 99%